Full-scale of composting process of biogas residues from corn stover anaerobic digestion: Physical-chemical, biology parameters and maturity indexes during whole process. (April 2020) - Meng, Xingyao; Yan, Jing; Zuo, Bin; Wang, Yunhe; Yuan, Xufeng; Cui, Zongjun
Graphical abstract: Highlights: Corn straw biogas residues is an ideal material for full-scale composting. The biogas residues get maturity after 80 days of composting. Temperature and NI was easily and credibly parameters to evaluate maturity. Anaerolineaceae and Limnochordaceae were the most abundant bacteria. Chaetomium was the most important fungal to decompose lignocellulose. Abstract: Recycling of biogas residues from corn stover anaerobic digestion is crucial for the development of biogas industry. Full-scale composting process is the feasible way to convert biogas residues to fertilizer. The aim of the study was to explore the feasibility of full-scale composting process to dispose biogas residue to fertilizer, and to evaluate the quality of the compost. The results showed the biogas residues could rapidly reach the thermophilic stage and last at least 20 days, NH4 + -N, TOC and C/N decreased along with the composting process, while TP, TK and NO3 – -N showed an opposite trend. Germination index(GI) and seedling growth index showed that raw biogas residues was toxic for plant, but the GI and seedling growth index were increased during the composting process, except for the cooling stage sample. Anaerolineaceae and Limnochordaceae were the main bacteria involved in the composting process, and Chaetomium was the most important fungus.